Differential Regulation of Two-Tiered Plant Immunity and Sexual Reproduction by ANXUR Receptor-Like Kinases. Issue 12 (17th November 2017) - Mang, Hyunggon; Feng, Baomin; Hu, Zhangjian; Boisson-Dernier, Aurélien; Franck, Christina M.; Meng, Xiangzong; Huang, Yanyan; Zhou, Jinggeng; Xu, Guangyuan; Wang, Taotao; Shan, Libo; He, Ping
Abstract : ANXUR receptor-like kinases regulate two-tiered plant immunity by association with pattern recognition receptor and NLR protein complexes. Abstract: Plants have evolved two tiers of immune receptors to detect infections: cell surface-resident pattern recognition receptors (PRRs) that sense microbial signatures and intracellular nucleotide binding domain leucine-rich repeat (NLR) proteins that recognize pathogen effectors. How PRRs and NLRs interconnect and activate the specific and overlapping plant immune responses remains elusive. A genetic screen for components controlling plant immunity identified ANXUR1 (ANX1), a malectin-like domain-containing receptor-like kinase, together with its homolog ANX2, as important negative regulators of both PRR- and NLR-mediated immunity in Arabidopsis thaliana . ANX1 constitutively associates with the bacterial flagellin receptor FLAGELLIN-SENSING2 (FLS2) and its coreceptor BRI1-ASSOCIATED RECEPTOR KINASE1 (BAK1). Perception of flagellin by FLS2 promotes ANX1 association with BAK1, thereby interfering with FLS2-BAK1 complex formation to attenuate PRR signaling. In addition, ANX1 complexes with the NLR proteins RESISTANT TO PSEUDOMONAS SYRINGAE2 (RPS2) and RESISTANCE TO P. SYRINGAE PV MACULICOLA1. ANX1 promotes RPS2 degradation and attenuates RPS2-mediated cell death. Surprisingly, a mutation that affects ANX1 function in plant immunity does not disrupt its function in controlling pollen tube growth during fertilization. Our study thus reveals a molecular link between PRR and NLR protein complexes that both associate with cell surface-resident ANX1 and uncovers uncoupled functions of ANX1 and ANX2 during plant immunity and sexual reproduction.